2020
DOI: 10.1093/cid/ciz1209
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity to Predict the Risk of Cytomegalovirus Infection in Kidney Transplantation: A Prospective, Interventional, Multicenter Clinical Trial

Abstract: Background Improving cytomegalovirus (CMV) immune-risk stratification in kidney transplantation is highly needed to establish guided preventive strategies. Methods This prospective, interventional, multicenter clinical trial assessed the value of monitoring pretransplant CMV-specific cell-mediated immunity (CMI) using an interferon-γ release assay to predict CMV infection in kidney transplantation. One hundred sixty donor/rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 29 publications
(36 reference statements)
1
74
0
Order By: Relevance
“…A recent multicenter double-blind randomized clinical trial included adult kidney transplant recipients who were anti-CMV antibody donor positive / recipient positive prior to transplantation ( 44 ). This clinical trial used T-SPOT®.CMV and assigned SOT recipients into the interventional groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent multicenter double-blind randomized clinical trial included adult kidney transplant recipients who were anti-CMV antibody donor positive / recipient positive prior to transplantation ( 44 ). This clinical trial used T-SPOT®.CMV and assigned SOT recipients into the interventional groups.…”
Section: Resultsmentioning
confidence: 99%
“…The cut-off to discriminate low- and high-risk SOT recipients were 20 spots per 300,000 PBMCs. Both low- and high-risk SOT recipients underwent randomization to receive either anti-CMV prophylaxis (for 3 months) or preemptive antiviral therapy ( 44 ). In addition, T-SPOT®.CMV was done 15 days post-transplantation in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…61 CMV peptides from the three following open reading frames (UL48, UL83, and UL123) are recognized by more than half of individuals. 48 Interestingly, IE-1 (UL123)-specific CD8 + T cells are associated with less CMV reactivation in SOTR, 62,63 probably because UL123 is the first CMV protein to be expressed in infected cells. In vitro, CMV-specific CD8 + T cells are able to exert antiviral effector functions trough interferon-γ (IFN-γ) production.…”
Section: Cmv-specific Cd8 + T Cellsmentioning
confidence: 99%
“…In patients undergoing CMV disease that are resistant to antiviral treatments, second-line therapies are associated with important adverse effects, and no other therapeutic option is currently available 5. Importantly, it has been shown that a quicker immune reconstitution of both αβ and γδ T cell compartments after HCT or a better quality of the αβ and γδ T cell responses in SOTR is correlated with a lower incidence of CMV infection and disease 34,63,[176][177][178]. These observations highlight the importance of an efficient cellular immune response for preventing CMV infection.Adoptive transfer of CMV-reactive T cells therefore represents an attractive approach in both HCTR and SOTR, in order to boost the cellular immune response and achieve long-term protection against CMV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation